Analisis Perbedaan Faktor Psikososial dalam Pemanfaatan Layanan Antenatal Care pada Remaja di Kota Jayapura - Lisda Oktavia Madu Pamangin; Christin Debora Nabuasa; Asriati Asriati; Natalia Paskawati Adimuntja; Fajrin Violita; Ade Alwi Imbiri; Isna Ainurrohimah; Muhammad Fajar Aswad Nugroho (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
The coverage of antenatal care in Papua has yet to meet the national target. This situation is consistent with the persistently high rates of maternal and child mortality. This study aims to analyse differences in perceptions, self-efficacy and social support based on the coverage of the six antenatal care visits (K6) among adolescents. A prospective study design was employed, with the study conducted in Jayapura City. The sample population consisted of all adolescents who had given birth. Sampling was carried out using purposive sampling, with a sample size of 102 respondents. Data collection was conducted through interviews using a questionnaire, which took place from 1 August to 9 September 2025. Data were analysed computationally using the Mann-Whitney test as the hypothesis test. The results showed differences in perception (p = 0.002), self-efficacy (p = 0.000), and social support (p = 0.001) between adolescents who utilised antenatal care based on the K6 coverage and those who did not. Based on these results, it can be concluded that psychosocial factors comprising perception, self-efficacy, and social support in adolescents are associated with their utilisation of antenatal care.Keywords: Teenage, antenatal care, perception, self-efficacy, social support